2015
DOI: 10.1016/j.apergo.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The use of virtual reality and physical tools in the development and validation of ease of entry and exit in passenger vehicles

Abstract: Setia (2015) The use of virtual reality and physical tools in the development and validation of ease of entry and exit in passenger vehicles. Applied Ergonomics, Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/32241/1/JLR%20entry%20exit%20paper_ePrints.pdf The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The future of Virtual Reality in the automotive industry of the development process, before expensive and time-consuming physical mock-ups are produced (Lawson and Burnett, in press., Lawson et al, 2015). Another utility of VR in design is the possibility of having multidisciplinary teams and teams spread across the world, to work together on the same prototype at the same time (Mujber et al, 2004).…”
mentioning
confidence: 99%
“…The future of Virtual Reality in the automotive industry of the development process, before expensive and time-consuming physical mock-ups are produced (Lawson and Burnett, in press., Lawson et al, 2015). Another utility of VR in design is the possibility of having multidisciplinary teams and teams spread across the world, to work together on the same prototype at the same time (Mujber et al, 2004).…”
mentioning
confidence: 99%
“…It is widely acknowledged that there is not yet comprehensive understanding of all factors affecting spatial perception, the specific effects of those factors, or of possible interactions between them. However, one suggestion in the literature is that haptic feedback may improve spatial judgements [3].…”
Section: Spatial Judgement In Virtual Environmentsmentioning
confidence: 99%
“…However, perception of distances in VEs is often inaccurate, which can lead to rejection of this technology by engineers or unsound decision making [11]. This can be an important limitation on perception tasks in engineering design when, for example, assessing elbow room in workstation design or judging access clearance and reach on a manufacturing line assembly task.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lawson et al [11] demonstrated that a CAVE could not give engineers the experience of getting in and out of a car, which is necessary for designing vehicle door apertures, due to the lack of physical hardpoints. One of their recommendations is to introduce haptic feedback to create the impression of contact with a vehicle surface.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation